Soberania e proteção dos direitos humanos frente à globalização econômica - Santos, Mikaele dos (2024)
The certainty of human evolution is a constancy that reflects transformations in the social structure. With this, this dissertation addresses an understanding of complementary conformity with the universalist premise of protecting human rights, from the sole paragraph, of article 4, of the 1988 Federal Constitution, to national sovereignty. To this end, it is intended to explore the issue of sovereignty in the face of economic globalization, due to the inefficiency of the State's isolated action in the protection of human rights. This is because the globalizing process demands the improvement of sovereignty beyond the political conception of territorial limits, which finds the possibility of mitigating the local negative effects of the expansion of the economic power of large corporations in cooperation between States. And in this scenario, through the hypothetical-deductive method regarding the study of sovereignty, which will be the initial point of understanding the topic, followed by the approach between market and society interaction today, and finally, the discussion of the legal aspects necessary to understand the constitutional legal viability, it can be seen from the social mechanisms inserted in the economic order of the CRFB/88 that the implications for state sovereignty of the normative possibility point to a convergence of complementary measures, whether through international cooperation without necessarily harming the performance of the State, or by direct action, when in the national interest.